2015
DOI: 10.5152/npa.2015.7472
|View full text |Cite
|
Sign up to set email alerts
|

The Psychiatric Consequences of Child and Adolescent Sexual Abuse

Abstract: Introduction: The purpose of this study was to investigate the psychiatric consequences of sexual abuse and its associated factors in children and adolescents referred to our child and adolescent psychiatry clinic from official medico-legal units.Methods: All victims of sexual abuse (n=590) aged 1-18 (mean: 13.56±3.38) referred from forensic units to Ondokuz Mayis University Child and Adolescent Psychiatry Clinic over a period of 2 years [boys: 83 (14.1%); girls: 507 (85.9%)] were included. Child and adolescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 59 publications
0
13
0
3
Order By: Relevance
“…Studies have shown that sexual violence against women leads to a number of problems including unwanted pregnancy, increased risk of HIV/AIDS infection and other sexually transmitted infections (STIs), gynecological problems, feeling of worthlessness, depression, fear and guilty feeling about sex, powerlessness, shame, difficulty in trusting people, post-traumatic stress disorder (PTSD), and even suicide [5,7,[16][17][18][19][20]. On top of that, it also exposes girls and women in schools to social consequences ranging from poor educational achievement to social withdrawal, having multiple partners, rejecting friends, drug and alcohol abuse, and even prostitution [15,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that sexual violence against women leads to a number of problems including unwanted pregnancy, increased risk of HIV/AIDS infection and other sexually transmitted infections (STIs), gynecological problems, feeling of worthlessness, depression, fear and guilty feeling about sex, powerlessness, shame, difficulty in trusting people, post-traumatic stress disorder (PTSD), and even suicide [5,7,[16][17][18][19][20]. On top of that, it also exposes girls and women in schools to social consequences ranging from poor educational achievement to social withdrawal, having multiple partners, rejecting friends, drug and alcohol abuse, and even prostitution [15,17,21].…”
Section: Introductionmentioning
confidence: 99%
“…The experience of sexual abuse can affect the development of children and adolescents in various ways, with frequent depression, anxiety, low self-esteem and social isolation [1][2][3][8][9][10][11][12]. Therefore, it is important to know the emotional state of these victims, as well as to understand the real needs they present for the establishment of the best therapeutic behavior capable of helping to improve their quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that children and adolescents who have been sexually abused may develop anxiety disorders, depressive and aggressive symptoms, problems with their role and sexual functioning, and serious difficulties in interpersonal relationships [11,12]. Thus, the complexity of the context lived by these young people requires a multiprofessional approach [13].…”
Section: O R I G I N a L A R T I C L Ementioning
confidence: 99%
“…İstismarcıların tamamının erkek olduğu ve %80,3'ünün mağdur tarafından tanındığı görülmüştür. İstismar mağdurlarının %73,2'sinin normal zeka aralığında, %12,3'ünün sınır zeka aralığında olduğu; %12,3'ünde hafif düzeyde zeka geriliği ve %1,8'inde ise orta düzeyde zeka geriliği olduğu saptanmıştır (20) .…”
Section: Introductionunclassified